Evaluation of Human Resource Management in the Indonesian Correctional System: Theoretical and Practical Perspectives - Rihan Lestari (Polteknik Pengayoman Indonesia, 2025)
This literature review examines the management of human resources (HR) within Indonesia's correctional system by integrating theoretical frameworks and empirical findings. The study analyzes key components including recruitment, placement, competency development, workload, motivation, and performance management of correctional officers. Findings indicate significant gaps between theoretical HR management principles and real-world practices, particularly in areas of competency alignment, training quality, psychological readiness, and workload balance. Structural challenges such as overcrowding and limited resources contribute to high levels of stress and burnout among officers. The review concludes that comprehensive HR reforms—encompassing competency-based recruitment, continuous training, improved welfare, and performance-based incentives—are essential to enhance the effectiveness of Indonesia’s correctional system.Keywords :